Journal of Police and Criminal Psychology The Official Journal of the Society for Police and Criminal Psychology - Herndon, James S.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Police and Criminal Psychology is a peer-reviewed journal that reports research findings regarding the theory, practice and application of psychological issues in the criminal justice context, namely law enforcement, courts, and corrections. The Journal encourages submissions focusing on Police Psychology including personnel assessment, therapeutic methods, training, ethics and effective organizational operation. The Journal also welcomes articles that focus on criminal behavior and the application of psychology to effective correctional practices and facilitating recovery among victims of crime. Consumers of and contributors to this body of research include psychologists, criminologists, sociologists, legal experts, social workers, and other professionals representing various facets of the criminal justice system, both domestic and international.
Keywords: Psychology; Psychology, general; Law and Psychology; Criminology and Criminal Justice, general